Solid-Phase Extraction of Trace Amounts of Uranium(VI) in Environmental Water Samples Using an Extractant-Impregnated Resin Followed by Detection with UV-Vis Spectrophotometry - Ahmad Hosseini-Bandegharaei; Masoud Sarwghadi; Aliasghar Heydarbeigi; Seyyed Hossein Hosseini; Mehdi Nedaie (Journal of Chemistry)
A stable extractant-impregnated resin (EIR) containing Chrome Azurol B was prepared using Amberlite XAD-2010 as a porous polymeric support. The new EIR was employed for trace separation and preconcentration of U(VI) ion followed by spectrophotometric determination with the arsenazo III procedure. CAB/XAD-2010 exhibited excellent selectivity for U(VI) ion over coexisting ions. Experimental parameters including pH, contact time, shaking speed, and ionic strength were investigated by batch extraction methods. Maximum sorption of U(VI) ions occurred at pH 4.3–6.9. The capacity of EIR was found to be 0.632 mmol·g−1. Equilibrium was reached in 25 min and the loading half-time, t1/2, was less than 6 min. The equilibrium adsorption isotherm of U(VI) was fitted with the Langmuir adsorption model. In addition, a column packed with CAB/XAD-2010 was used for column-mode separation and preconcentration of U(VI) ion. For the optimization of the dynamic procedure, effects of sample volume, sample and eluent flow rate, eluent concentration, and its volume were investigated. The preconcentration factors for U(VI) were found out to be 160. But, for convenience, a preconcentration factor of 150 was utilized for the column-mode preconcentration. The dynamic procedure gave a detection limit of 5.0×10-10 mol·L−1 (0.12 μg·L−1) for U(VI) ion. The proposed dynamic method showed good performance in analyzing environmental water samples.